Мовні засоби вираження порівняльних конструкцій у французькому художньому дискурсі(на матеріалі роману Ясміна Кадра "Чим день завдячує ночі") - Мартинюк, Оксана; Martyniuk, Oksana (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Досліджуються основні види порівнянь, які використовуються у худож ньому дискурсі. Характеризуються шляхи використання автором стилістичного прийому порівняння для характеристики зовнішності героїв, дій, процесів, явищ природи тощо. Описано лексико -граматичні моделі порівняння. З точки зору семантики порівняння у художньому дискурсі можна поділити на такі групи: які виражають фізичні, інтелектуальні та емоційні характеристики. Об’єктом порівнянь можуть виступати будь-які явища дійсності. Найчастіше порівнюються люди, їх зовнішність, характери, здібності з тваринами, рослинами, предметами, явищами природи. Виявлено, що важливими у порівнянні є не самі компоненти, а ті асоціації, які виникають у результаті мовного порівняння. Проаналізовано інтерактивні можливості порівняння: вплив на адресата тексту, управління його комунікативно-пізнавальною діяльністю відповідно до задуму автора. Доведено, що порівняння допомагають розкрити багатство асоціативних відтінків художнього мовлення, оскільки є механізмом вербалізації психоемоційного стану героїв.The article examines the main types of comparisons that are used in the discourse. The ways of using by the author a stylistic device for comparing the characteristics of the characters appearance, actions, processes, phenomena of nature, and so on are characterized. The lexical and grammatical models of comparison are described. In terms of semantics comparative constructions in the discourse can be divided into the following groups: comparisons of expressing physical characteristics, intellectual and emotional characteristics. Any real phenomenon can serve the object of comparisons. Most often people, their appearance, character, ability are compared with animals, plants, objects, natural phenomena. It was revealed also that in comparative constructions the components themselves are not so important, but those associations that arise as a result of linguistic comparison. The interactive features of comparison were analysed, namely the impact on the recipient of the text, the management of its communicative and cognitive acti vity in accordance with the intent of the author. It is proved that the comparison helps to reveal the wealth of associative nuances of artistic speech, as it is the mechanism of verbalization of mental and emotional state of the characters.
Language Means of Expression of Comparative Constructions in the French literary discourse (on the material of the novel of Yasmin Khadr “What the Day Owes the Night”)
Keywords: троп; порівняння; асоціація; характеристика; лексико-граматичні моделі; trope; comparisons; association; characterization; lexical and grammatical models